Cautery ablation of a remote recurrent tracheoesophageal fistula - Sara Fallon; Wesley Barry; Jeremy Jackson; Joseph Edmonds; Eugene Kim (Elsevier, 2018)
Complications subsequent to repair of a congenital tracheoesophageal fistula (TEF) with esophageal atresia (EA) include leak at the anastomosis, stricture formation, and recurrent fistula. Recurrence is uncommon, and the optimal management for a recurrent fistula is debatable. As many of the symptoms of TEF recurrence are similar to common postoperative sequelae, diagnosis of these recurrences can be quite challenging. We report the case of a 12 year old patient with a history of Type B EA/TEF (proximal pouch fistula, distal atresia) who was discovered to have a TEF recurrence over a decade after his initial repair which was successfully treated with cautery ablation of the fistula tract.